2020
DOI: 10.1186/s40104-020-00490-x
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction alters growth performance, plasma hormones, and small intestinal microbial communities in growing-finishing pigs

Abstract: Background: The interaction of the gut microbiota with key metabolic and physiological processes may be associated with poor growth outcomes in animals born with intrauterine growth restriction (IUGR). Results: Growth performance, plasma hormone concentrations, and intestinal microbiota composition were analyzed in IUGR pigs and in normal birth weight (NBW) pigs when the NBW pigs reached 25, 50, and 100 kg of body weight (BW). Compared to NBW pigs, IUGR pigs had lower initial, weaned, and final BW, and lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 51 publications
8
38
0
Order By: Relevance
“…Intestinal flora is the crucial determinant of intestinal development and immune system maturation. Previous studies revealed that low birth weight can disturb gut microbiota [ 31 , 34 ], which was confirmed by the present study. Proteobacteria is one of the dominant phyla of gram-negative bacteria, consisting of various harmful pathogens, such as Escherichia and Actinobacillus [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Intestinal flora is the crucial determinant of intestinal development and immune system maturation. Previous studies revealed that low birth weight can disturb gut microbiota [ 31 , 34 ], which was confirmed by the present study. Proteobacteria is one of the dominant phyla of gram-negative bacteria, consisting of various harmful pathogens, such as Escherichia and Actinobacillus [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the defective antioxidant system of the IUGR intestines may contribute to uncontrolled oxidative stress and subsequent local and systemic damage, thereby decreasing the growth performance of young animals [ 7 ]. Recently, researchers proposed that the changes in intestinal microbiota communities of IUGR pigs are associated with their poor growth outcomes [ 31 , 34 ]. The present study demonstrated that both RSV and its derivative PT retained jejunal villus-crypt architecture, prevented jejunal excessive apoptosis, and maintained the intestinal integrity of IUGR piglets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, gut microbiota is dynamically diverse within limits and influenced by multiple factors such as species, age, sex, diet, and health status ( Manichanh et al, 2012 ; Wang et al, 2020 ; Xiong et al, 2020 ; Zhu et al, 2020 ). Several studies have indicated that diarrhea was able to cause a significant decrease in the diversity of gut bacterial community as well as shifts in intestinal functions ( Barash et al, 2017 ; He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant to note that LBW pigs at birth have been associated with different microbial post-weaning profiles [17,20] and also as growing and adult animals [19,26]. For instance, the LBW pigs had a lower abundance of Ruminococcaceae UCG-005 but a higher abundance of Ruminococcaceae UCG-014 on Days 21 and 32, respectively [19] The IUGR pigs presented higher microbial diversity in the jejunum and ileum in the growing and finishing phases which has been associated with a lower performance [26]; at 25 kg of BW, they had a higher level of unclassified Ruminococcaceae in the ileum and lower Ochrobactrum abundance in the jejunum while, at 50 and 100 kg, they had higher Firmicutes abundance but lower Proteobacteria abundance in the jejunum and lower Lactobacillus abundance in the jejunum and ileum [26]. Overall, the differences in the microbial profile of LBW pigs could be associated with a different development of mucosal immunity since it is known that the intestinal microbiome and mucosal immunity are strictly related [27].…”
Section: Birth Body Weight and Physiological Maturationmentioning
confidence: 99%